Smoking and Depression among Healthcare Workers - Ghimire, Madhusudhan; Sharma, Achala; Ghimire, Moushami (Journal of Lumbini Medical College, 2016)
Introduction: Healthcare workers are a special public icon for the community because people would like to adopt and implement their knowledge, skill, attitude and behaviour for improving quality of health. People respect them for their knowledge and health behavior. It is believed that the level of health status of health workers as well as community should go ahead parallel but many researchers have noted that high risk behaviours (smoking, tobacco use, alcoholism, irregular diet intake, lack of exercise etc.) are prevalent among health workers. The result of this will be physical, psychological, familial and social disturbance, which might have an impact on health care delivery system of the country. The study was concerned to assess health status (body mass index, smoking and depression) of healthcare workers and its impact on social adjustment in Banke district of Nepal.Methods: A cross sectional study design was applied to conduct the research. One hundred and eight respondents were selected through random sampling from the purposive group. Data wa collected through interview by using interview schedule. SPSS-16 windows process was used to analyze data.Results: Most of the respondent (81.40%) were under the age group less than 30 years (M = 27.35, SD = 9.24 years). More than 57.40% of respondents were female. Most of them (68.50%) were unmarried. Maximum (82.20%) responders had normal Body Mass Index (18.5-24.99). Near about forty percent (38.9%) healthcare worker had faced social problems in their working area.Conclusion: Age (above 20 years) and male healthcare workers were more likely to smoke cigarettes. Depressed health workers were more likely to smoke cigarette. Depression could be observed as a determinant for social adjustment.Journal of Lumbini Medical College. 2014;2(1):21-24.